Concepções norteadoras da prática pedagógica de professoras da educação infantil e uso pedagógico da culinária: possíveis relações - Silva, Leilany Fernandes Rodrigues Arruda da (Universidade Federal de São Carlos, 2002)
This work, of qualitative kind, searches for understanding the two pre-school teachers' conceptions by analysing their teaching resources regarding cookery activities in classroom. In order to make it possible, the data were got in their own classrooms having children aged six under their responsability and taking place in a public school of S.Carlos' Municipal Educational Net. Since S.Carlos'Municipal Education deals with Teaching Projects, the researcher intervened by developing cookery experiences related to the subjects and objectives of these same projects in order to verify the conceptions assumed by both teachers starting from the teaching utilization the teachers are supposed to do with the different themes. The work presents as initial hypothesis that teachers' own conceptions change into elements that will interfer with teaching experiences and, at same time, they are going to constitute and change themselves in their confront with reality. This kind of movement doesn't occur in a linear and straight way. In order to understand better the actual context where both participant teachers were insered, the researcher tried to understand how works the Teaching Projects studying the Teaching Projects as a teaching proposal and tried also to find out the underlied conceptions supporting them. The data's analyse obtained allowed us to realize that there are in the teaching experiences conceptions that the own teachers have about the teaching process and can belong to differents kinds of models such as authoritary, spontaneous or democratic. (FREIRE, 1977) The different moments lived during the work, the confrontation between the collected data and the theories supporting them, all this could provide us elements for some considerations: -the construction of an effective teaching experience, able to offer students significant , cheerful and vibrant learnings compromised with the respect of the students considered as historical and social beings. This process can not be acquired neither by the only adotion of techniques nor the only utilization of democratic and socializant methodologies; -the conceptual changes are to be derived from a substantial education able to shake hard stablished models, able to reveal the unconscious conceptions. This education won't be certainly obtained in a no-systematic way; -the school comes to be the place where one can potentially interfere in teachers' models, if this is desirable, and in this way able to promove the exercise of reflexion and theorization about the necessary experiences to aim this aim.
Keywords: Educação; Concepções de educação; Prática pedagógica; Culinária - educação; Educação infantil; Metodologia de ensino.; Pedagogical practice; Cooking in education; Early Childhood Education; Conceptions of education; CIENCIAS HUMANAS::EDUCACAO